The Effect of Audio Visual Health Education Method on Increasing Adolescent Girls' Knowledge About Personal Hygiene During Menstruation - Tri Peni; Heri Triwibowo; Sindy Aprilia (Kirana Publisher (KNPub), 2023)
Adolescence is a period of transition from childhood to adulthood. Puberty for girls is marked by the onset of menstruation. The lack of knowledge among young women in carrying out personal hygiene can be at risk for the growth of microbes that cause vaginal odor and vaginal discharge to occur. This causes various diseases of the reproductive organs. One way to increase knowledge is by providing health education. This study aims to determine the effect of audio-visual media health education on increasing female adolescent knowledge about personal hygiene during menstruation. The research design used a one-group pretest-post-test design. The population in this study were all 7th-grade female students of SMP 3 Silo, totaling 59 students. The sampling technique of this research is accidental sampling. The research sample is 54 respondents. The research instrument used a questionnaire. Data analysis using the Wilcoxon Signed Rank Test. The results showed that almost all respondents had sufficient knowledge before being given health education, namely 45 people (83.3%), and almost all respondents had good knowledge after being given health education, namely 43 people (79.6%). The results of the Wilcoxon test showed that p-value = 0.000 so there was an effect of audio-visual media health education on increasing knowledge about personal hygiene during menstruation. Audiovisual aids are capable of displaying moving pictures, writing, and animation accompanied by sound so that it is not boring and the information received is clearer and more quickly understood.